Evaluating Organisational Change and Employee Productivity in Nigeria: A Case Study of Union Bank, Plc - Igudia, Patrick Ohunmah (European Scientific Journal, ESJ, 2021)
This study examined the effects of organisational change on employee productivity in the banking sector in Nigeria. Following a comprehensive literature review, the study identified technological, cultural, employee attitude to change, leadership, and change in customers’ taste as the change strategies that can facilitate competitive advantage and attainment of set organisational goals. The primary data collection method was adopted employing questionnaire strategy. 102 respondents were selected as sample size. The study used the multiple regression statistical analysis through SPSS statistical package version 25 for analysis. The overall results revealed that organisational change has a positively significant impact on employee productivity. To this effect, technological, leadership, attitudinal and cultural changes in that order highly impact employee productivity in Union Bank even though they were rarely used to implement change. As a result, Union bank is advised to embrace convergent change management so as to be better equipped to maintain excellence in productivity and overcome external challenges such as competition. On the contrary, changes especially in customer taste do not influence the productivity of employees, perhaps due to the nature of their business operations (service). The study recommends among others that while implementing firm’s improvement strategies, Union Bank managers should look at the organisation’s technological change models, cultural change, employees’ attitude to change, and leadership change against their primary competitors.